Histological tissue healing following high‐power laser treatment in a model of suspensory ligament branch injury. (20th January 2022) - Pluim, Mathilde; Heier, Annabelle; Plomp, Saskia; Boshuizen, Berit; Gröne, Andrea; van Weeren, René; Vanderperren, Katrien; Martens, Ann; Dewulf, Jeroen; Chantziaras, Ilias; Koene, Marc; Luciani, Antonio; et al.
Summary: Background: High‐power laser therapy gained popularity recently as a regenerative treatment for tendinitis and desmitis in the horse. However, studies evaluating the effects of laser therapy on tissue repair at the histological level in large mammals are lacking. Objectives: To evaluate the effects of high‐power laser therapy on suspensory desmitis healing, using a model of suspensory ligament branch injury. Study design: In vivo experiments. Methods: Standardised lesions were surgically induced in all four lateral suspensory branches of 12 healthy Warmblood horses. Laser therapy (class 4, 15W) was applied daily on two of four induced lesions for four consecutive weeks. Horses were randomly assigned to either short‐term study (horses were sacrificed after 4 weeks) or long‐term study (6 months). Suspensory ligament samples were scored after staining with haematoxylin‐eosin and immunostaining for collagen 1‐ collagen 3‐ and factor VIII. Results: In the short‐term study, significantly better (lower) scores for variation in density (17% above cut‐off score in treated lesions vs. 31% above cut‐off score in controls, P = .03), shape of nuclei (54% vs 92%, P = .02), fibre alignment (32% vs 75%, P = .003) and fibre structure (38% vs 71%, P = .02) were found in laser‐treated lesions when compared to controls. Collagen 3 expression was significantly higher (32% vs 19%, P = .006) in control lesions. In both short‐ and long‐term studies combined, parameters lesion size (44% vs 56%, P = .02) and shape of nuclei (53% vs 84%, P = .05) scored significantly better in treated lesions. Long‐term, significantly better (lower) scores were found in the laser‐treated group for lesion size (15% vs 45%, P = .008) and a higher percentage above cut‐off score for density of the nuclei (27% vs 9%, P = .02), compared to controls. Main limitations: The model of suspensory branch injury is not an exact representation of clinical overstrain lesions. Conclusions: These results suggest that high‐power laser therapy enables better lesion healing than conservative treatment.